Drag Reduction on How to Improve Fuel Consumption of a Vehicle - Kamarul Ariffin B Kasnin, Kamarul Ariffin (Universiti Teknologi Petronas, 2010)
The aim of this project is to provide a study on the aerodynamics profile of a vehicle (Perodua Viva) and ways to reduce drag to improve its fuel consumption. The methods used to reduce the drag are by tapering the rear, covering the wheel wells and also by having a smooth, lowered underbelly. A drag coefficient is a number that indicates the car’s aerodynamics smoothness. A bigger, bulkier car often has higher coefficient of drag. Higher drag coefficient causes the car to do more work when driven. More work done by the engine causes more fuel to be burned. Often we see that for two vehicles with the same engine capacity driven at the same speed, the car having bigger coefficient of drag will consume more fuel